Augmented Reality and Learning Motivation in Achieving 21st Century Skills: The Mediating Role of Immersive Learning Experiences - Budi Riyanto; Riki Wanda Putra; Arya Widiatmaja; Hasri Devin; Cris Kuntadi; I Kadek Laju; Bambang Hermanto (IJECA (International Journal of Education and Curriculum Application), 2025)
In response to the increasing demands for 21st-century competencies, this study adopts an explanatory quantitative research design to investigate the mediating role of Immersive Learning Experiences (ILE) in the relationship between Augmented Reality (AR) and Learning Motivation (LM) toward the acquisition of 21st-Century Skills (CS). Using a quantitative explanatory design with Partial Least Squares Structural Equation Modeling (PLS-SEM), this study analyzes data from Generation Z students (aged 17–25) enrolled at the Ministry of Transportation's maritime campus in Sumatra to evaluate this relationship. The results show that AR has a significant positive effect on ILE (β = 0.603; t = 3.878; p < 0.001), while its direct effect on 21st-Century Skills (CS) is negative and insignificant (β = -0.225; t = 1.461; p = 0.144). ILE, in turn, significantly influenced CS (β = 0.599; t = 4.928; p < 0.001) and significantly mediated the effect of AR on CS (β = 0.361; t = 2.924; p = 0.003). Meanwhile, Learning Motivation (LM) did not show a significant direct or indirect effect on CS through ILE. This finding highlights that ILE plays a significant mediating role in linking AR to 21st-century skills, while LM did not show a comparable influence. This suggests that intrinsic factors such as motivation are crucial, with technology-enhanced learning environments playing a more dominant role in developing 21st-century skills. The limited mediation effect of ILE in the LM–CS pathway may stem from the inherently cognitive–affective nature of motivation, which may require different pedagogical support. Future research is recommended to incorporate moderator variables such as digital literacy and adopt a longitudinal design to assess the sustained impact of immersive learning on skill development.